Tongue hematoma and psychomotor agitation in the course of alcohol use disorder - case report - Paweł Stanicki; Maciej Dobosz; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2019)
Excessive alcohol consumption can have many repercussions. Cirrhosis, injuries and infectious diseases are the most common. The following case report shows a patient admitted to the emergency department due to swelling of the tongue that prevented speaking. Laboratory tests showed elevated levels of markers of liver damage: AST, GGTP, total bilirubin, CRP. Prolonged INR, APTT and platelet deficiency were also discovered. This indicated bleeding due to alcoholic cirrhosis as a diagnosis. The patient was given, among others, diuretics and corticosteroids, after which a decrease in hematoma has been observed. The patient was transported to the Otolaryngology Department. On the same day he attacked the doctor and freed himself from physical coercion which was applied. As a result of these events he was transferred to a neuropsychiatric hospital. Described case indicates a correlation between a deficiency of coagulation factors and the formation of a hematoma of the tongue. It also emphasizes the importance of being cautious about patients who may experience sudden changes in behavior for neurological reasons.